A importância das células ciliadas externas para a discriminação de fala na presença de ruído competitivo - Andrade, Kelly Cristina Lira de (2017)
The different types of day-to- day noise interfere directly in speech comprehension. In oral communication situations, hearers must select the desired speech signal while ignoring all adjacent noise in order to understand the message. The auditory system consists of afferent and efferent auditory pathways that act jointly, and the olivocochlear bundle is a well known circuit within the efferent system. Among the functions attributed to the medial efferent system is improved detection of acoustic signals in the presence of noise. Given that efferent auditory pathways can be activated by suppressing otoacoustic emissions and that this occurs due to the action of fibers in the medial olivocochlear tract via external ciliated cell synapses, and that the speech stimulus familiar to the hearer may be a determining factor for improved speech comprehension in situations of listening with competitive noise, the aim of this study was to assess the importsnce of external ciliated cells in discriminating speech in the presence of competitive noise. This evaluation was initially conducted based on the effect of suppressing transient-evoked otoacoustic emissions in normal hearers in the presence of different suppressor stimuli. Next, familiar speech recognition in the presence of different types and intensities of competitive noise was evaluated. Furthermore, also as a study objective and due to the gap observed during psychoacoustic classes, we propose to develop a device that could contribute to knowledge acquisition of students in terms of speech intelligibility in different noise environments as well as sound localization. To assess the effect of otoacoustic emission suppression, we assessed eight individuals of both sexes, aged between 22 and 26 years, submitted to transient-evoked otoacoustic emission recordings, white noise suppression, white noise and pure tone suppression at 1kHz, auditory training, new recording of white noise and pure tone suppression at 1 kHz, suppression using standard speech and with the “happy birthday to you” song with a familiar voice as suppressor noise. After this pilot study and methodologicsl adjustments, 15 individuals of both sexes, aged between 20 and 37 years were submitted to the following procedures: transient-evoked otoacousrtic emission recordings, emission suppression with white noise, balanced sentences from the Hearing in Noise Test - Brazil protocol and the “happy birthday to you” song. To assess familiar speech recognition, 21 individuals of both sexes, aged between 20 and 35 years were submitted to otoscopy, immittance testing, tonal and vocal audiometries and sentence recognition tests in the presence of competitive noise. It was concluded that all the stimuli used were able to suppress otoacouistic emissions at 1 kHz, and greater suppression was observed with speech stimuli when compared to white noise, also at 1kHz. Familiar speech recognition in normal-hearing adults is higher than that of standard speech with white noise at an intensity of 55 dBSL above the speech recognition threshold.